IMF Survey, Volume 35, Issue 05. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2006)
IMF pandemic preparations; enlarged EU: labor, capital; Asia outlook bright; India: reforms and growth; Italy: gloomy outlook; IMF sanctions on Zimbabwe; Friedman: morals, growth; central bank communications; effective use of increased aid.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet